2014
DOI: 10.1155/2014/529293
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Mode Control for Active Suspension System with Data Acquisition Delay

Abstract: This paper addresses the problem of control of an active suspension system accomplished using a computer. Delay in the states due to the acquisition and transmission of data from sensors to the controller is taken into account. The proposed control strategy uses state predictors along with sliding mode control technique. Two approaches are made: a continuous-time and a discrete-time control. The proposed designs, continuous-time and discrete-time, are applied to the active suspension module simulator from Quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…For a nonlinear active suspension system with bounded uncertainty and external disturbance, the sliding mode control (SMC) has the advantage of robustness to improve the antidisturbance ability of the system. In [16], the state predictors along with SMC technique are applied to active suspension system, which consider the time delay of the data transmission. Mixed control strategies are proposed in [17], and an enhanced adaptive self-fuzzy sliding mode controller for a quarter-car active suspension system is presented.…”
Section: Introductionmentioning
confidence: 99%
“…For a nonlinear active suspension system with bounded uncertainty and external disturbance, the sliding mode control (SMC) has the advantage of robustness to improve the antidisturbance ability of the system. In [16], the state predictors along with SMC technique are applied to active suspension system, which consider the time delay of the data transmission. Mixed control strategies are proposed in [17], and an enhanced adaptive self-fuzzy sliding mode controller for a quarter-car active suspension system is presented.…”
Section: Introductionmentioning
confidence: 99%
“…where ρ is a positive constant. To reduce the effect of chattering in the control law (36), a modified control law is used (Alves et al, 2014) u n ðtÞ ¼ Àρ…”
Section: Smcmentioning
confidence: 99%
“…Numerous advanced control strategies such as sliding mode control (SMC), H-infinity, fuzzy, and backstepping (Rath et al, 2015) have been proposed for the vibration control of active suspension systems in the literature (Alves et al, 2014; Trikande et al, 2018). SMC in combination with the inertial delay observer is proposed in Gupta et al (2016), where uncertainties are canceled out, and states are observed simultaneously, thus reducing the sensor requirement.…”
Section: Introductionmentioning
confidence: 99%
“…Another group [13] performed a coordinate transformation to convert a time-delay system into a time-delay-free system. Yet another group [14,15] converted the time-delay into an error of the secondary path and reduced the effect of time-delay using error control. One study [16] conducted in-depth research of time-delay in magneto-rheological dampers.…”
Section: Introductionmentioning
confidence: 99%